Long‐term viral suppression and immune recovery during first‐line antiretroviral therapy: a study of an HIV‐infected adult cohort in Hanoi, Vietnam. Issue 4 (6th December 2017) - Tanuma, Junko; Matsumoto, Shoko; Haneuse, Sebastien; Cuong, Do Duy; Vu, Tuong Van; Thuy, Pham Thi Thanh; Dung, Nguyen Thi; Dung, Nguyen Thi Hoai; Trung, Nguyen Vu; Kinh, Nguyen Van; Oka, Shinichi
Abstract: Introduction: Achieving viral suppression is key in the global strategy to end the HIV epidemic. However, the levels of viral suppression have yet to be described in many resource‐limited settings. Methods: We investigated the time to virologic failure (VF; defined as a viral load of ≥1000 copies/ml) and changes in CD4 counts since starting antiretroviral therapy (ART) in a cohort of HIV‐infected adults in Hanoi, Vietnam. Factors related to the time to VF and impaired early immune recovery (defined as not attaining an increase in 100 cells/mm 3 in CD4 counts at 24 months) were further analysed. Results: From 1806 participants, 225 were identified as having VF at a median of 50 months of first‐line ART. The viral suppression rate at 12 months was 95.5% and survival without VF was maintained above 90% until 42 months. An increase in CD4 counts from the baseline was greater in groups with lower baseline CD4 counts. A younger age (multivariate hazard ratio (HR) 0.75, vs. <30), hepatitis C (HCV)‐antibody positivity (HR 1.43), and stavudine (d4T)‐containing regimens (HR 1.4, vs. zidovudine (AZT)) were associated with earlier VF. Factors associated with impaired early immune recovery included the male sex (odds ratio (OR) 1.78), HCV‐antibody positivity (OR 1.72), d4T‐based regimens (OR 0.51, vs. AZT), and nevirapine‐based regimens (OR 0.53, vs. efavirenz) after controlling for baseline CD4 counts. Conclusion: Durable high‐rate viral suppression was observed in the cohort of patients on first‐line ART in Vietnam. Our results highlight the need to increase adherence support among injection drug users and HCV co‐infected patients.